Optical study on relaxation of excitons and initiation of photopolymerization in diacetylene crystals at low temperatures - Chihiro Itoh (International Journal of Photoenergy)
Luminescence and optical absorption induced by irradiating with a pulse of 266nm laser beam have been measured in 5,7-dodecadiyne-1,12-diol bis[phenyl carbamate] (DA-TCDU). In addition to the recombination luminescence of the lowest triplet state, luminescence from the excited single state is identified. Irradiation with a pulse of 266 nm laser beam having the fluence above 4.4 mJcm-2 leads to formation of series of optical absorption bands at 3.05 eV, 2.52 eV and 2.18 eV, which are ascribed to the optical transition due to dimer diradicals, trimer diradicals and the tetramer diradicals, respectively. The laser-fluence dependence of the integral intensity of the recombination luminescence of the singlet and the triplet exciton and the absorption strength of the 3.05 eV band have been measured. The nature of the triplet exciton and its relation to the initiation of the photopolymerization are discussed.